Identification and validation of novel engineered AAV capsid variants targeting human glia - Giacomoni, Jessica; Åkerblom, Malin; Habekost, Mette; Fiorenzano, Alessandro; Kajtez, Janko; Davidsson, Marcus; Parmar, Malin; Björklund, Tomas (Frontiers in Neuroscience, 2024)
Direct neural conversion of endogenous non-neuronal cells, such as resident glia, into therapeutic neurons has emerged as a promising strategy for brain repair, aiming to restore lost or damaged neurons. Proof-of-concept has been obtained from animal studies, yet these models do not efficiently recapitulate the complexity of the human brain, and further refinement is necessary before clinical translation becomes viable. One important aspect is the need to achieve efficient and precise targeting of human glial cells using non-integrating viral vectors that exhibit a high degree of cell type specificity. While various naturally occurring or engineered adeno-associated virus (AAV) serotypes have been utilized to transduce glia, efficient targeting of human glial cell types remains an unsolved challenge. In this study, we employ AAV capsid library engineering to find AAV capsids that selectively target human glia in vitro and in vivo. We have identified two families of AAV capsids that induce efficient targeting of human glia both in glial spheroids and after glial progenitor cell transplantation into the rat forebrain. Furthermore, we show the robustness of this targeting by transferring the capsid peptide from the parent AAV2 serotype onto the AAV9 serotype, which facilitates future scalability for the larger human brain.